Zora Neale Hurston's Final Decade - Moylan, Virginia Lynn (Book collections on Project MUSE., 2011)
From Publishers Weekly: Moylan's goal-"to freshly interpret" Zora Neale Hurston's tumultuous final decade, rocked by scandal and the author's controversial political views-is ill-met by this well-intentioned but clunky biography. Moylan, founding member of the Fort Pierce, Fla., Annual Zora Festival, draws heavily on two texts (Valerie Boyd's biography Wrapped in Rainbows, and Carla Kaplan's edition of Hurston's letters, Zora Neale Hurston: A Life in Letters), supplemented by a number of interviews with the employers, acquaintances, and friends of Hurston's last decade. After a brief biographical sketch of Hurston's early years, Moylan addresses, in term-paperish prose, the false child molestation charges that, even after they were recanted, left Hurston's reputation in tatters, and her very controversial (in Moylan's words, "eccentric") objections to Brown v. Board of Education and desegregation on the grounds that, in her perspective, "racial uplift" would come by individual effort alone. Hurston's final creative projects-her development of an "anthropologically correct" black baby doll and planned biography of King Herod attest to how the famously idiosyncratic and iconoclastic writer remained deeply unpredictable and fascinating, and that her "lost years" merit a thoughtful and thorough biography. Unfortunately, this meandering, amateurish account isn't it